Design and methods of the 'monitoring outcomes of psychiatric pharmacotherapy' (MOPHAR) monitoring program - a study protocol - Mirjam Simoons; Henricus G. Ruhé; Eric N. van Roon; Robert A. Schoevers; Richard Bruggeman; Daniëlle C. Cath; Diny Muis; Johan Arends; Bennard Doornbos; Hans Mulder (BMC, 2019)
Abstract Background At many outpatient departments for psychiatry worldwide, standardized monitoring of the safety of prescribed psychotropic drugs is not routinely performed in daily clinical practice. Therefore it is unclear to which extent the drugs used by psychiatric outpatients are prescribed effectively and safely. These issues warrant structured monitoring of medication use, (pre-existing) co-morbidities, effectiveness and side effects during psychiatric outpatient treatment. Improvement of monitoring practices provides an opportunity to ensure that somatic complications and adverse drug effects are detected and dealt with in a timely manner. Structural support for data collection and follow-up tests seems essential for improvement of monitoring practices in psychiatric outpatients. The implementation of a structured somatic monitoring program as part of routine clinical practice, as we describe in this study protocol, may be a solution. Methods In order to address these issues, we developed the innovative program 'Monitoring Outcomes of Psychiatric Pharmacotherapy (MOPHAR)'. MOPHAR is an infrastructure for implementation of standardized routine outcome monitoring (ROM; including standardized monitoring of treatment effect), monitoring of adverse psychotropic medication effects in psychiatric outpatients, encompassing both somatic adverse effects (e.g. metabolic disturbances) and subjective adverse effects (e.g. sedation or sexual side effects) and medication reconciliation. Discussion In the MOPHAR monitoring program, a nurse performs general and psychotropic drug-specific somatic screenings and provides the treating mental health care providers with more and better information on somatic monitoring for treatment decisions. Given our experience regarding implementation of the MOPHAR program, we expect that the MOPHAR program is feasible and beneficial for patients in any MHS organisation. This paper describes the objectives, target population, setting and the composition and roles of the treatment team. It also indicates what measurements are performed at which time points during outpatient treatment in the MOPHAR monitoring program, as well as the research aspects of this project. Trial registration MOPHAR research has been prospectively registered with the Netherlands Trial Register on 19th of November 2014. (NL4779).